Implementasi Sistem Absensi Karyawan Berbasis Web Menggunakan QR Code Dinamis yang Berubah Secara Berkala pada Objek CV. My Bakery - Irfan Dani; Vidi Sandi (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2026)
Employee attendance management plays a crucial role in a company’s human resource management process. Conventional attendance systems are still prone to fraudulent practices, such as buddy punching, which may reduce the reliability of attendance records. This research aims to develop and implement a web-based employee attendance system utilizing dynamic QR Codes at CV My Bakery. The system development adopted the Waterfall methodology consisting of requirement analysis, system design, implementation, testing, and maintenance stages. The application was developed using PHP with the CodeIgniter framework and MySQL database management system, while QR Code generation employed the PHPQRCode library. The implemented system is capable of generating dynamic QR Codes that automatically change periodically, minimizing the possibility of attendance fraud through reused screenshots or QR Code images. Based on black-box testing results, all system functionalities operated as expected. The system includes features such as admin and employee authentication, dynamic QR Code generation, QR-based attendance scanning, attendance time recording, and attendance report management. The implementation of this system contributes to improving the effectiveness and accuracy of employee attendance management at CV My Bakery.